Estimation of natural reproduction efficiency of semi-anadromous and river fish species in inland water bodies of the Republic of Dagestan, Russia - A. S. Abdusamadov; E. A. Akhmaev; A. A. Latunov; T. A. Abdusamadov; A. K. Butaeva; S. A. Guseinova (Юг России: экология, развитие, 2020)
Aim. Estimation of the natural reproduction efficiency and patterns of formation of fish stocks.Material and Methods. Collection of material was carried out in 2010-2019 in inland water bodies in Dagestan and its shallow Caspian Sea coastal zone. Estimation of the number of juveniles in rivers and canals was carried out using ichthyoplankton cone seines. Fry seines were used to count juveniles of fish in water bodies and in the coastal area. 470 samples of juveniles were collected and 5640 juveniles were analysed. The collection and processing of materials were carried out according to generally accepted methods.Results. The main environmental factors determining the productivity of fish juveniles in the study area in the long-term have been identified. During the observation period, juvenile fish of 15 species were recorded in spawning grounds of inland water bodies. Roach, bream, carp, crucian carp, rudd and vimba bream dominate. In terms of numbers, roach juveniles predominate: their relative proportion being 31.02% with an increase from 27.1% in 2010 to 35.4% in 2018.The second place was occupied by bream juveniles, whose average relative proportion was 12.1%. The third place was occupied by carp juveniles with an average proportion of 9%. Juvenile zander, catfish, pike and kutum are relatively low in abundance from 2 to 4%. The yield of juvenile fish in 2010-2019 decreased 1.7 times compared to 1990-1995.Conclusion. It was established that a decrease in the number of juvenile fishes occurs under the influence of unfavorable environmental factors: decrease in sea level; reduction in spawning areas; the shallowing and silting of migration routes due to the lack of a stable water supply. Measures are proposed to improve the living conditions of aquatic biological resources, aimed at increasing the efficiency of their natural reproduction.